MEDIA FRAMING ON ONLINE NEWS HEADLINES IN REGARDS TO THE GILETS JAUNES PHENOMENON - Myrna Laksman-Huntley; Fastira Dwiputri (Universitas Hasanuddin, 2020)
Gilets Jaunes massive protest in France was considered as the most serious crisis in the Fifth Republic since the protest of May 1968. The importance of the event was such that it generated serious controversy, which was widely reported and many French media competed to highlight the development of the action group. This study examines the headlines of the Gilets Jaunes phenomenon in two online news sites (LeFigaro.fr and Libération.fr) with a different ideology. The analysis was carried out using theories of Le Querler's syntactic structure, Nida's meaning componential analysis, Dor & Gattani's headline functionality, and Entman's media framing. The results show that left-wing media news titles framed Gilets Jaunes as evidence of the people's struggle, while the right-wing media framed Gilets Jaunes as an action that only caused riots and casualties.